2012
DOI: 10.1021/ol301107m
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of Graphisin A and Sydowinin B

Abstract: Efficient syntheses of the highly substituted benzophenone graphisin A and the xanthone sydowinin B are described. Key steps involve aryl anion addition to substituted benzaldehyde derivatives, subsequent methyl ester installation, and dehydrative cyclization. Oxidation of graphisin A led to a spirodienone derived from a highly substituted benzoquinone intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…Engyodontiumone A ( 1 ) had a molecular formula of C 17 H 14 O 7 as established by HRESIMS ( m/z 331.0801 [M + H] + ). Its NMR data ( Table 1 and Table 2 ) was similar to that of sydowinin B [ 5 , 6 ] with the only difference of one methoxyl (δ C 56.8) and the absence of a hydroxyl proton signal in 1 , which indicated that 1 was a chromone skeleton. In the HMBC spectrum (see Supporting Information Figure S3 ), correlations of δ H 12.11 with C-7/C-8/C-13 suggested a hydroxyl group located at C-8, correlations of δ H 3.88 (3H, s) with C-2 suggested a methoxy group located at C-2, and correlations of δ H 4.60 (2H, s) with C-5/C-6/C-7 suggested a hydroxymethene group attached at C-6.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Engyodontiumone A ( 1 ) had a molecular formula of C 17 H 14 O 7 as established by HRESIMS ( m/z 331.0801 [M + H] + ). Its NMR data ( Table 1 and Table 2 ) was similar to that of sydowinin B [ 5 , 6 ] with the only difference of one methoxyl (δ C 56.8) and the absence of a hydroxyl proton signal in 1 , which indicated that 1 was a chromone skeleton. In the HMBC spectrum (see Supporting Information Figure S3 ), correlations of δ H 12.11 with C-7/C-8/C-13 suggested a hydroxyl group located at C-8, correlations of δ H 3.88 (3H, s) with C-2 suggested a methoxy group located at C-2, and correlations of δ H 4.60 (2H, s) with C-5/C-6/C-7 suggested a hydroxymethene group attached at C-6.…”
Section: Resultsmentioning
confidence: 72%
“…Engyodontiumone B ( 2 ) had a molecular formula of C 16 H 11 ClO 6 as inferred from its HRESIMS ( m/z 335.0309 [M + H] + ) showing peaks at m/z 335.0309 and 337.0264 with the height ratio of 3:1. Its NMR data ( Table 1 and Table 2 ) showed great similarity to those of sydowinin B [ 5 , 6 ] with the only obvious difference of the high-field shift of the chemical shift of C-2 (from δ C 148.9 in sydowinin B to δ C 125.5 in 2 ) suggesting the loss of the hydroxyl functionality. Combined with the molecular formula and HMBC spectral data (see Supporting Information Figure S8 ), these data suggested a chlorine atom attached at C-2.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We initially prepared the aldehyde derivative and PT‐sulfone as substrates of the Julia–Kocienski olefination (Scheme ). Aldehyde 12 was synthesized by a sequential operation of bromination of commercially available 2,5‐dihydroxybenzaldehyde ( 10 ) and MOM protection of the two phenolic hydroxyl groups ( 11 ) (Scheme a). PT‐sulfone 9 was obtained through the Mitsunobu reaction of 1‐phenyl‐1 H ‐tetrazol‐5‐yl thiol (PT‐SH) with n ‐hexanol ( 13 ) followed by oxidation of the sulfide to sulfone (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
“…which could be prepared in decagram scale and good enantiomeric purity in 4 steps from aldehyde 9 21,22) and 1-phenyl-1Htetrazol-5-yl (PT)-sulfone 10, by Julia-Kocienski olefination, asymmetric Shi epoxidation, 23) BF 3 -OEt 2 mediated epoxide opening, and Pd-catalyzed C1 insertion/lactonization cascade reaction [24][25][26][27] (Chart 2). The propargyl moiety was introduced by the treatment of 8 with 3-chloro-3-methylbut-1-yne in the presence of 1,8-diazabicyclo [5.4.0] undec-7-ene (DBU) and catalytic amount of CuCl 2 to afford propargyl derivative 7 in good yield.…”
Section: Highlighted Paper Selected By Editor-in-chiefmentioning
confidence: 99%